Influence of silver-ion-containing pharmacotherapeutic system for repair of anterior abdominal wall on connective tissue formation in experiment - Ekaterina S. Mishina; Maria Zatolokina; Anastasia V. Gureeva; Vladimir V. Gureev; Karina A. Elagina; Eugenia S. Zatolokina (Belgorod National Research University, 2019)
Introduction: In modern medicine new pharmacotherapeutic systems significantly reducing the risk of complications are being actively searched for. The study undertaken was aimed at studying one of such systems consisting of a prosthesis coated with silver ions. Materials and methods: The material for the study was standard endoprostheses produced by Lintex LLC (St.-Petersburg) for plastic repair of the anterior abdominal wall: Esfil and Uniflex, as well as Plasmofilter produced by Plasmofilter JSC (St.-Petersburg) and a pharmacotherapeutic system containing silver ions (FCS) applied to the experimental samples of endoprostheses - Esfil Ag and Unifleks Ag (patent RU 2473369C1), which were implanted into male Wistar rats. The results were evaluated using morphological, morphometric, immunohistochemical, ionometric, microbiological and statistical methods. Results and discussion: As a result, it was found that the use of the FCS leads to a more rapid change in inflammation phases. The formation of a mature connective tissue capsule with a thickness of 4.5±0.01 mm was observed by Day 30. The study of the cellular component of the periprosthetic tissue revealed the prevalence of resident cells. The proliferative activity of fibroblastic cells when using FCS over 14 days was statistically significantly (p≤0.05) 3.5-time higher. Microbiological studies confirmed the antibacterial properties of FCS in vivo and in vitro. Conclusion: The use of FCS contributes to the acceleration of reparative processes, earlier resolution of inflammation and stimulation of collagenesis both under sterile conditions and under microbial conditions.